Memoria archivada del chisme. Análisis de un caso de infidelidad mediática - Solís López, Augusto-Pavel (2024)
The article aims to analyze the discourse of infidelity gossip in a Peruvian show business couple, focusing on the construction of memory about infidelity in the social network X during the year 2024. A descriptive qualitative analysis technique is employed based on a selection of 115 highlighted tweets collected from the X API, with the terms Christian Domínguez and Pamela Franco. The analysis focuses on the categories of monogamy, cheating and infidelity information according to gender. The results indicate that there is a difference in the interpretation of the memory of infidelity in the case of Dominguez, with a greater scope and conversations that use humor as part of the discourse. In contrast, in the case of Franco, more judgments about his behavior are observed, as well as assessments related to his emotions and body, and a lower presence of humor. In conclusion, the mediatization of gossip in Peru does generate distinctions about who is considered unfaithful, influenced by gender and the personal history of each individual in relation to this behavior.